2011
DOI: 10.1007/s12149-011-0470-6
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET for the diagnosis of fever of unknown origin: a Japanese multi-center study

Abstract: FDG-PET for the diagnosis of FUO provided additional diagnostic information and had a high clinical impact, especially among patients with infectious diseases. It was also helpful in cases with unknown or other miscellaneous diseases by allowing the exclusion of focally active diseases. The prevalence of diseases in hospitals significantly affected the effectiveness of FDG-PET for the diagnosis of FUO. FDG-PET is a useful examination providing various degrees of clinical impact for the management of FUO, depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 22 publications
(27 reference statements)
2
27
0
Order By: Relevance
“…• Evaluation of fever of unknown origin (FUO) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), including true FUO (defined according to the criteria of Durack and Street (44)), postoperative fever and recurrent sepsis, immunodeficiency (both induced and acquired)-related FUO, neutropenic fever, and isolated acute-phase inflammation markers (persistently raised C-reactive protein and/or erythrocyte sedimentation rate).…”
Section: Common Clinical Indicationsmentioning
confidence: 99%
“…• Evaluation of fever of unknown origin (FUO) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), including true FUO (defined according to the criteria of Durack and Street (44)), postoperative fever and recurrent sepsis, immunodeficiency (both induced and acquired)-related FUO, neutropenic fever, and isolated acute-phase inflammation markers (persistently raised C-reactive protein and/or erythrocyte sedimentation rate).…”
Section: Common Clinical Indicationsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Similarly, PET is also now used to detect inflammation 78 that is due to both infectious diseases, such as fever of unknown origin (FUO) and bacteremic foci, [79][80][81] and non-infectious diseases, such as graft rejection in liver and renal transplants. [82][83][84][85] We have recently shown that inflammatory cytokines induce autophagy in cancer-associated fibroblasts, consistent with a shift toward aerobic glycolysis under inflammatory conditions.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Whole body positron emission tomography (PET) or combination of PET with computed tomography (PET/ CT) using 18 F-fluorodeoxyglucose (FDG) is a relatively common examination in patients with fever of unknown origin (FUO) or low-grade fever with non-specific symptoms [17][18][19][20] . Patients with GCA and PMR can therefore undergo these examinations in the course of differential diagnosis of inflammatory or malignant disease.…”
Section: Introductionmentioning
confidence: 99%